Knowledge and practice on medication adherence among type II diabetes mellitus patients - Mohammad, Nurfatihah Masrurah; Hassan, Masmunaa; Jamaludin, Thandar Soe Sumaiyah (2019)
This study aimed to survey the level of knowledge and practice on medication adherence among Type 2 Diabetes Mellitus patients among Type 2 Diabetes Mellitus (DM) patients in Malaysia. A cross-sectional study was conducted in an outpatient department at (HTAA) with convenience sample of 220 DM patients. A self-administered questionnaire comprising of 27 items was administered to the participants. Majority of the participants were between the age of 51 and 70 years old. Among all of them, 35% were using both OHA and insulin therapy as their diabetes treatment (n=77). Study findings revealed that 64.5% obtained high level of knowledge with good practice towards medication adherence. The socio-demographic characteristics were associated with high knowledge (p-value; age=0.039, gender= 0.047, educational level=0.000 & duration of diabetes=0.000) and good practice (p-value; age=0.023, gender= 0.047, educational level=0.000 & duration of diabetes=0.027) towards medication adherence. The results of this study showed that majority of patients had high knowledge and good adherence towards medication compliance. However, this information should be used in clinical practice when targeting and designing educational and care plan for T2DM patients to achieve desired glycemic control. The outcome of this study could give some input to health care providers to improve their patient’s care by playing their important role in promoting importance of knowledge on medication adherence for a better quality of life to the patients. Instead of physician, nurse could enhance education on medication during appointment for diabetes. Continuous follow-up and assessment could be constantly inspected to determine their progress outcomes.